1669 kū chīp nai kū phai (phibat) : thō̜t prasopkān rabop kānphǣt chukchœ̄n nai sathānakān namthūam læ din thalom Phāk Tai, Prathēt Thai - Thitinop Kōmonnimi (Sathāban Kānphǣt Chukchœ̄n hǣng Chāt, 2011)
On measures taken and cooperation between various organizations and agencies for future preparation for landslide and flood disaster in Southern Thailand.